Relações entre os estilos parentais e juízo moral de adolescentes - Kadooka, Aline [UNESP] (2015)
Studies on how parents are educating their children have been conducted in the parenting styles approach. Parents are responsible for providing the first information to the children, because in the preschool period are primarily responsible for the provision of material and emotional resources. In educational practice, the parents when interact with their children or through their own behavior, transmit norms and values to children and adolescents and therefore contribute to the moral development of the same. In educational practice, the parents when interact with their children or through their own behavior, transmit norms and values to children and adolescents and therefore contribute to the moral development of the same.This interaction influences in the repertoire of tools that will be used to cope with the different situations in life. The rules, actions, judgments and values that parents express contribute to the mode of being of the child. From the point of view of moral psychology,, parents can be good or bad models, since they are inevitably their examples. When teens practice and experience the rules in accordance with the cooperation and not by external pressures or obedience, they are able to elaborate them differently. Hence the importance of mutual respect and dialogue for the way to the moral autonomy. This study aimed to analyze the relationship between moral reasoning teens and parenting styles. Participated in this study 55 adolescents between 11 and 17 years enrolled in a Social Program Assis-SP. To achieve the proposed objectives, we use as instruments the Respondingness and Demandingness Scale and the Defining Issues Test (DIT-2). It is worth mentioning that the Scheme of Interest Staff comprises the lower levels of moral development, ie the pre-conventional level. The results obtained in this study indicate that the participants mainly showed a level of pre-conventional and conventional moral reasoning. In relation to...